Neurofilament Levels Are Reflecting the Loss of Presynaptic Dopamine Receptors in Movement Disorders - Diekämper, Elena; Brix, Britta; Stöcker, Winfried; Vielhaber, Stefan; Galazky, Imke; Kreissl, Michael C.; Genseke, Philipp; Düzel, Emrah; Körtvelyessy, Péter (Frontiers in Neuroscience, 2021)
Aims: Neurofilament light Chain (NfL) and phosphorylated Neurofilament heavy Chain (pNfH) are biomarkers for neuroaxonal damage. We assessed, whether NfL and other biomarker levels in the CSF are correlated to the loss of presynaptic dopamine transporters in neurons as detected with dopamine transporter SPECT (DaTscan). Methods: We retrospectively identified 47 patients (17 Alzheimer Dementia, 10 idiopathic Parkinson Disease, 7 Lewy Body Dementia, 13 Progressive Supranuclear Palsy or Corticobasal Degeneration) who received a DaTscan and a lumbar puncture. DaTscan imaging was performed according to current guidelines and z-scores indicating the decrease in uptake were software-based calculated for the nucleus caudatus and putamen. The CSF biomarkers Progranulin, Total-Tau, Alpha-Synuclein, NfL and pNfH were correlated with the z-scores. Results: DaTscan results in AD patients did not correlate with any biomarker. Subsuming every movement disorder with nigrostriatal neurodegeneration resulted in a strong correlation between putamen/nucleus caudatus and NfL (nucleus caudatus right p<0.01, putamen right p<0.05, left p<0.05) and between pNfH and putamen (right p<0.05; left p<0.042). Subdividing in disease cohorts did not reveal significant correlations. Progranulin, Alpha-Synuclein and Total¬-Tau did not correlate with DaTscan results. Conclusions: We show a strong correlation of NfL and pNfH with pathological changes in presynaptic dopamine transporter density in the putamen concomitant to nigrostriatal degeneration. This correlation might explain the reported correlation of impaired motor functions in PD and NfL as seen before despite the pathological heterogeneity of these diseases.